2018
DOI: 10.5603/ep.a2018.0029
|View full text |Cite
|
Sign up to set email alerts
|

Badanie zależności między metylacją regionu promotora genu MMP-9 a nefropatią cukrzycową

Abstract: Introduction: This study aims to explore the relationship between the methylation of matrix metalloproteinase (MMP)-9 gene promoter region and diabetic nephropathy (DN) through the detection of the methylation level of MMP-9 gene promoter region in the peripheral blood of patients with DN in different periods and serum MMP-9 concentration. Material and methods: The methylation level of the MMP-9 gene promoter region was detected by methylation-specific polymerase chain reaction (MSP), and the content of MMP-9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 14 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…The kidney's matrix metalloproteinases (MMPs), a class of endopeptidases, that are zinc-dependent, possessing comparable biochemical characteristics, are connected to both regular physiological alterations and irregular pathological disorders ( Yang et al, 2018 ). MMP-9 might be crucial for leukocyte migration and regional extracellular matrix proteolysis.…”
Section: Introductionmentioning
confidence: 99%
“…The kidney's matrix metalloproteinases (MMPs), a class of endopeptidases, that are zinc-dependent, possessing comparable biochemical characteristics, are connected to both regular physiological alterations and irregular pathological disorders ( Yang et al, 2018 ). MMP-9 might be crucial for leukocyte migration and regional extracellular matrix proteolysis.…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation is one of the most common epigenetic changes, and numerous studies have shown that gene hypermethylation promotes the occurrence of DN. [4][5][6][7] The number of differentially methylated regions (DMRs) in DN is significantly higher than that in diabetes without nephropathy. 8 Therefore, reducing the hypermethylation status represents a novel approach for DN treatment.…”
Section: Introductionmentioning
confidence: 99%